Technical efficiency of some selected manufacturing industries in Bangladesh: A stochastic frontier analysis - Baten, Md Azizul; Rana, Masud; Das, Sumonkanti; Khaleque, Md Abdul (Lahore School of Economics, 2006)
This paper investigates the technical efficiency of selected manufacturing industries of Bangladesh using a stochastic frontier production function approach suggested by Battese and Coelli (1992) applied to panel data.A feasible Cobb-Douglas stochastic frontier production function, which has time-varying technical inefficiency effects, was estimated.Two alternative distributions were used to model the random inefficiency term: a truncated normal distribution and a halfnormal distribution.The estimated average technical efficiency for four groups of industries of Bangladesh over the reference period was 40.22% of potential output for the truncated normal distribution, whereas it was 55.57% of potential output for the half-normal distribution.